2018
DOI: 10.3389/fpsyg.2018.00648
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Efficacy, Work Engagement, and Social Support Among Chinese Special Education School Teachers

Abstract: This paper investigates the relationship between teacher efficacy and socio-demographic factors, work engagement, and social support among Chinese special education school teachers. The sample comprised 1,027 special education school teachers in mainland China. The Teachers’ Sense of Efficacy Scale, the Multi-Dimensional Scale of Perceived Social Support, and the Utrecht Work Engagement Scale were used for data collection. Correlation analysis revealed that social support, work engagement, and teacher efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
90
0
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 38 publications
16
90
0
14
Order By: Relevance
“…Accordingly, it is necessary to enhance the emotional intelligence of teachers who belong to group 2 (high EE and DE) because superior emotional and self-regulation skills are essential to the alleviation of high degrees of exhaustion. Similarly, it is necessary to improve the following, especially among teachers who belong to group 2: the illusion at work (Dalcin and Carlotto, 2018); the perceived effectiveness of teachers (i.e., individual and collective) and job satisfaction (Guidetti et al, 2018;Minghui et al, 2018;Molero et al, 2019;Von Der Embse et al, 2019); welfare and commitment (Skaalvik and Skaalvik, 2018); adaptive working conditions (Chambers Mack et al, 2019;Eurofound, 2019); the social support of coworkers; effective support to meet family demands and prevent role conflict between work and family demands (i.e., personal exhaustion that results from work overload can worsen the family situation; e.g., it can reduce the quality of care that is provided to family members); and time management skills (De Carlo et al, 2019;Eurofound, 2019;World Health Organization [WHO], 2019). It is also important to reduce role ambiguity by clarifying the responsibilities of each professional (Carlotto and Câmara, 2019;De Carlo et al, 2019;Eurofound, 2019;Molero et al, 2019) and minimize the tediousness of administrative procedures (Carlotto and Câmara, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is necessary to enhance the emotional intelligence of teachers who belong to group 2 (high EE and DE) because superior emotional and self-regulation skills are essential to the alleviation of high degrees of exhaustion. Similarly, it is necessary to improve the following, especially among teachers who belong to group 2: the illusion at work (Dalcin and Carlotto, 2018); the perceived effectiveness of teachers (i.e., individual and collective) and job satisfaction (Guidetti et al, 2018;Minghui et al, 2018;Molero et al, 2019;Von Der Embse et al, 2019); welfare and commitment (Skaalvik and Skaalvik, 2018); adaptive working conditions (Chambers Mack et al, 2019;Eurofound, 2019); the social support of coworkers; effective support to meet family demands and prevent role conflict between work and family demands (i.e., personal exhaustion that results from work overload can worsen the family situation; e.g., it can reduce the quality of care that is provided to family members); and time management skills (De Carlo et al, 2019;Eurofound, 2019;World Health Organization [WHO], 2019). It is also important to reduce role ambiguity by clarifying the responsibilities of each professional (Carlotto and Câmara, 2019;De Carlo et al, 2019;Eurofound, 2019;Molero et al, 2019) and minimize the tediousness of administrative procedures (Carlotto and Câmara, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, social support is highly significant in fostering Chinese special education student teachers. Lu et al (2018) surveyed 1,027 special education teachers in China and found that although their social support directly affects their self-efficacy, it also exerts an indirect effect on their self-efficacy through work engagement. However, the aforementioned studies have been aimed at in-service teachers, and whether such a relationship exists among preservice teachers remains unknown.…”
Section: Social Support and Asementioning
confidence: 99%
“…Professional identity is defined as a person's sense of belonging to and recognition of the profession (Tickle, 1999), which has an important influence on individual career learning and engagement. Furthermore, the public remains unfamiliar with the special education profession and has biased views of special education teachers (Lu et al, 2018). Taken together, these factors may affect the ASE of preservice special education teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Se han utilizado múltiples constructos de gran relevancia para poder comprender los resultados de aprendizaje, académicos y niveles de grado y logro. Enunciemos algunos de ellos: la motivación de logro (ej., atribuciones), la autoeficacia percibida, las actitudes, las características personales, los estilos de aprendizaje y de pensamiento, el uso de estrategias, factores de inteligencia emocional, los procesos de autorregulación, entre otros, lo que permite contrastar con muchos estudios internacionales recientes en el campo (Barrio & Barrio, 2018), incluyendo estudios internacionales de comparación con muestras colombianas (Cheng y Lin, 2018; Cuesta et al, 2018; Díaz y García, 2016a; García-Martín y García-Sánchez, 2017;Habok y Magyar, 2017;Karagiannopoulou et al, 2018, Mnez-Ferrer et al, 2018Minghui et al, 2018;Oriol et al, 2018;Puente et al, 2018;Robledo y García, 2018;Romera et al, 2018, Sinval et al, 2018Widlund et al, 2017;Zheng et al, 2019). En una revisión reciente, en que se analizan todas las intervenciones pedagógicas con enfoque en la autorregulación, implementadas en China durante las últimas dos décadas, de 603 estudios, sólo pudieron incluirse en los análisis 59, y de ellos se identifican solo cuatro estudios cuasiexperimentales, frente al resto observacionales (Li et al, 2018, ver también Xie et al, 2018, lo que confirma el estado general a nivel, no solo de Colombia o de USA (Scott et al, 2018, ver también Miller et al, 2017, también en Europa (Uttl et al, 2017, van Ockenburg, 2019) sino generalizado (ver el impresionante meta-análisis de Peng et al, 2019), por lo que la justificación de esta investigación y con la metodología prevista, es una opción con potencial heurístico, de contribución teórica y aplicada.…”
Section: Antecedentes Del Papel De Variables Psicoeducativasunclassified